2015
DOI: 10.1080/10494820.2014.997248
|View full text |Cite
|
Sign up to set email alerts
|

The benefits of a challenge: student motivation and flow experience in tablet-PC-game-based learning

Abstract: Advances in technology have led to continuous innovation in teaching and learning methods. For instance, the use of tablet PCs (TPCs) in classroom instruction has been shown to be effective in attracting and motivating students' interest and increasing their desire to participate in learning activities. In this paper, we used a TPCs gamean iPad app called Motion Math: Hungry Fish -to help young students learn to theoretically understand and practically implement the mathematical concepts of addition and subtra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
66
1
12

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 147 publications
(87 citation statements)
references
References 62 publications
8
66
1
12
Order By: Relevance
“…Such design not only motivated students but helped them gain a sense of achievement. The result supports findings of da Rocha Seixas, et al (2016) and Hung et al (2015). Additionally, this study further explores the potential of simple challenge design in which the sub-goals, the rewards, and levels are simple and direct rather than complex or too visual-oriented feedback.…”
Section: Significant Interaction Effects On Learning Achievement Of Asupporting
confidence: 75%
See 2 more Smart Citations
“…Such design not only motivated students but helped them gain a sense of achievement. The result supports findings of da Rocha Seixas, et al (2016) and Hung et al (2015). Additionally, this study further explores the potential of simple challenge design in which the sub-goals, the rewards, and levels are simple and direct rather than complex or too visual-oriented feedback.…”
Section: Significant Interaction Effects On Learning Achievement Of Asupporting
confidence: 75%
“…Fullagar, Knight, & Sovern, 2013;Hung, Sun, & Yu, 2015). Previous studies indicated that students would learn how to overcome the given challenges that typically start off easy-levels and then become more difficult when students' abilities improve (Hamari et al, 2016;McGonigal, 2011).…”
Section: Game-challengementioning
confidence: 99%
See 1 more Smart Citation
“…In the game-based learning and gamification contexts specifically, studies predict that learning and gamified curricula will become more and more commonplace as a method to invoke engagement and flow in students (Crisp, 2014). Moreover, studies have found these technologies do indeed invoke flow experiences Procci, Singer, Levy, & Bowers, 2012) and have the potential to affect consequent learning outcomes (Barzilai & Blau, 2014;Brom et al, 2014a;Chang, Wu, Weng, & Sung, 2012;Hung, Sun, & Yu, 2015;Liu, Cheng, & Huang, 2011;Sabourin & Lester, 2014) although there are also studies that find no significant association (e.g. Brom, Bromov a, D echt erenko, Buchtov a, & Pergel, 2014b).…”
Section: Introductionmentioning
confidence: 96%
“…tactile, visual and auditory) experiences, but also motivate them to actively engage in immersive learning (Hung, Sun, & Yu, 2015). It is because the touchscreens of mobile devices serve as a congenial interface for students to intuitively interact with the virtual objects in the games simply by tapping and sliding on the screens with their fingertips (Hung et al, 2015).…”
Section: Introductionmentioning
confidence: 99%